PENGEMBANGAN BAHAN AJAR MENGGUNAKAN FLIP PDF PROFESSIONAL PADA MATERI MATRIKS - Nona Frike Manumpil; Jhon R. Wenas; Anetha L.F. Tilaar (CV. ADIBA AISHA AMIRA, 2022)
The lack of use of technology makes learning monotonous as well as the packaging of teaching materials that are less attractive makes students bored to learn mathematics so that solutions are needed to create or develop teaching materials in which the teaching materials are packaged attractively and help mathematics learning activities. The purpose of this research is to develop matrix teaching materials by utilizing or using professional flip pdfs and to determine the quality of teaching materials from the aspects of validity, practicality, and effectiveness of the developed teaching materials. Research and Development (R&D) with the ADDIE development model used in this study. The percentage of validity of the assessment by expert I 83%, expert II 95%, expert III 92% where the results are in the valid and very valid criteria. The practicality of the matrix teaching materials based on the average student response is 89% with very practical criteria, while the teacher's response on the presentation results is 92% with very practical criteria. The effectiveness of matrix teaching materials based on student learning outcomes tests with a mastery percentage of 82.85% is in the very effective criteria. So, the conclusion is that the matrix material teaching materials developed are valid, practical and effective for use in the learning process.